Hydatid disease in children: a single centre study with analysis of treatment protocol - Mishra, Atul; Patel, Kalpesh (International Surgery Journal, 2020)
Background: Hydatid disease or hydatidosis is a zoonosis which is still an important health hazard in the world. This disease is a parasitic infestation which is endemic in many sheep and cattle raising areas of the world including India. The aim of this study was to evaluate the clinical features, diagnosis, and treatment of hydatid cyst in pediatric population. Methods: This prospective study evaluated 32 pediatric patients with hydatid cyst who were treated at Geetanjali Hospital, Udaipur from 2016-2018. Medical records of these patients were studied and analyzed. Results: 32 cases were in the age group of 7 to 14 years and were from rural background/ farming community and of low socioeconomic status. Male children, lungs were predominantly involved. Cattle rearing were common to the households of all patients. Ultrasonography and computed tomography scan were done in all patients and was the main diagnostic modality. All cases were managed surgically along with albendazole therapy and had complete recovery with no recurrence till date in any of our patients. Conclusions: Hydatid disease is not rare in the pediatric age group. The liver and lung are commonly involved, but it may also present as primary disease in unusual sites like the spleen and brain. Careful surgery to avoid spillage with full course of drug therapy with albendazole can ensure permanent cure. A 28 day post-operative course was sufficient in majority of the cases. The disease can be prevented by proper community based measures like availability of clean water, sanitation and drug prophylaxis.